PENGARUH BAHASA ARAB TERHADAP IDENTITAS SOSIO-KULTURALDAN KEAGAMAAN MASYARAKAT KOPTIK DI MESIR - Yoyo, Yoyo (Arabic Letters and Department, 2017)
In general, Arabic is the official language of the Arab states. However, at the beginning of its contact with non-Arab societies, this language—that is always associated as the language of Islam—was not easily accepted by non-Muslims. One of them is Coptic community, the native of Egyptian people who are Christians and speak Coptic language. The spread of the Arabic language was a serious challenge for them both from the issue of social identity, culture, and religion. This paper attempts to elaborate the reactions and efforts made by the Coptic community on the influence of the Arabic language to their lives. In detail, the paper tries to answer research questions as follow: 1) Howwas the social and political background of Coptic community before and after the coming of Islam in Egypt? 2) How was the Islamization and Arabization process in Egypt? Did the process run concurrently or two things different from its periode? What is the influence of the Arabic language on socio cultural and religious aspects of the Coptic community? To arrive at these objectives, the author used descriptive analysis methods by reviewing previous studies related to the subject and combining it with current information. The results showed that: 1) from the socio-cultural side, Arabic has become Coptic identity that can be seen from their Arabic names and their integration as part of both in ritual and religious literature.